Study of surface roughness and its effect on the Nusselt number of circular microchannel - Sapkota, Shuveksha; Darlami, Hari Bahadur (Journal of Innovations in Engineering Education, 2025)
Miniaturization is playing an increasingly important role in ensuring the sustainability of energy systems and increasing their efficiency. In the current design environment, a high heat transfer rate with minimal pumping power is a key consideration. Microchannels are distinguished by flow and heat transfer in restricted microscopic geometries. The numerical simulation and analytical calculations were carried out in circular microchannels to evaluate roughness and its effect on the value of the Nusselt number. The dataset of available experimental investigations was cited, and the study was conducted using water as the working fluid and steel as the working medium, with Reynolds numbers ranging from 400 to 3200. Surface roughness is investigated as a result of homogeneous distribution at the microscale. This study focuses primarily on the Nusselt number, with simulated values of 4.0590 and 4.1347 for smooth channels and regular rough channels, respectively.